(Improving Learning Outcomes Learners by Implementing Cooperative Learning Model Round Table Type on the Main Line Network in Plant in Class XI MIPA 2 SMA Negeri 2 Pekanbaru): MENINGKATKAN HASIL BELAJAR PESERTA DIDIK DENGANMENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE ROUND TABLE PADA POKOK BAHASAN JARINGAN PADA TUMBUHAN DI KELAS XI MIPA 2 SMA NEGERI 2 PEKANBARU - Rahayu, R.R Sri (Perspektif Pendidikan dan Keguruan, 2018)
Learning is essentially a process of interaction with all situations around individuals. Learning can be viewed as a process directed to the goals and processes of doing through various experiences. Learning is also a process of seeing, observing, and understanding things. In the learning process there are two activities that interact, namely learning activities and teaching activities.Learning is an active activity of learners in building meaning or understanding. Activity learners in undergoing learning activities is one key to success to improve learning outcomes. Optimal learning outcomes are the main goals to be achieved in the learning process. To optimize the learning outcomes of learners required methods and learning models in accordance with teaching materials. The learning process can be done in school, at home, or in the place of study guidance. For learning in school, learners are exposed to a number of subjects, one of them is biology subjects. Biology is one of the subjects received by students in high school. Biology is the study of the structure contained in living things. More simply can be said that biology is closely related to daily life. What we experience, what we do, why it happened and why. Subjects in the subject of biology are generally theoretical, but also the ability of learners to understand the concept to link learning with daily life. One of the biology subject matter in the form of conceptual or theoretical understanding is tissue in plants.